Periodontal ligament stem cell-based bioactive constructs for bone tissue engineering - Zhao, Zeqing; Liu, Jin; Weir, Michael D.; Schneider, Abraham; Ma, Tao; Oates, Thomas W.; Xu, Hockin H. K.; Zhang, Ke; Bai, Yuxing (Frontiers in Bioengineering and Biotechnology, 2022)
Objectives: Stem cell-based tissue engineering approaches are promising for bone repair and regeneration. Periodontal ligament stem cells (PDLSCs) are a promising cell source for tissue engineering, especially for maxillofacial bone and periodontal regeneration. Many studies have shown potent results via PDLSCs in bone regeneration. In this review, we describe recent cutting-edge researches on PDLSC-based bone regeneration and periodontal tissue regeneration. Data and sources: An extensive search of the literature for papers related to PDLSCs-based bioactive constructs for bone tissue engineering was made on the databases of PubMed, Medline and Google Scholar. The papers were selected by three independent calibrated reviewers. Results: Multiple types of materials and scaffolds have been combined with PDLSCs, involving xeno genic bone graft, calcium phosphate materials and polymers. These PDLSC-based constructs exhibit the potential for bone and periodontal tissue regeneration. In addition, various osteo inductive agents and strategies have been applied with PDLSCs, including drugs, biologics, gene therapy, physical stimulation, scaffold modification, cell sheets and co-culture. Conclusoin: This review article demonstrates the great potential of PDLSCs-based bioactive constructs as a promising approach for bone and periodontal tissue regeneration.